The capital maintenance regime matters for creditors - Tadeusz Dudycz; Paweł Mielcarz (Borsa İstanbul Review, 2023)
Relying on an unbalanced panel of 25,211 observations of Polish unlisted companies for the period 2005-2018, we employ panel data analysis to investigate the role of the capital maintenance principle in securing creditors' interests. We document a persistently higher level of indebtedness among firms that adhere to the capital maintenance regime. Although the strength of the relationship is contingent on debt maturity, capital maintenance is found to be significant for both adjusting creditors, who can adjust the terms of the loan contract correspondingly to the credit risk and non-adjusting creditors. Unlimited liability is shown to eliminate the need to maintain legal capital, thus demonstrating the notable role of legal capital in safeguarding creditors' interests in cooperation with limited liability companies. In contrast to the viewpoint of advocates for abandoning legal capital requirements, we show that legal capital remains an important mechanism for ensuring compatibility in incentives between shareholders and creditors.
Keywords: 330; Capital maintenance regime; Creditor rights protection; Debt capacity; Liability